Astropolitics: Yes, That Is Really a Thing - Bohumil Doboš (Međunarodni Problemi, 2020)
The paper reviews the main approaches towards the study of the geopolitics of outer space and presents some main issues to be tackled in the future. Geopolitics, as an approach towards the analysis of international politics, generally discusses the impact of geography on the political processes. Throughout history, approaches to analyse the impact of different types of terrain or different types of environment (sea, air, land) on the conduct of political activity were developed. It was only in the 1990s when Everett Dolman applied the geopolitical approach to the outer space domain. Since then, many approaches to the issue were developed, and the stream known as astropolitics became an important stream of academic thought. The author analyses some physical characteristics necessary for the understanding of the domainʼs mechanisms and then presents some important streams of thought inside the geopolitical thinking. The analysis focuses on the issues of actorness, the relations between space powers, technological progress, the introduction of space weapons, utilisation of natural resources, and sustainability of space operations. The author concludes that with foreseeable technological progress in the future, the outer space domain will become more relevant for both academia and practitioners in their approach to international politics, requiring deeper understanding of how processes in this domain can impact political events and relations.